The journal's first year of publication and the challenges ahead - Israeli Avi; Rosen Bruce (BMC, 2012)
Abstract The Israel Journal of Health Policy Research (IJHPR) seeks to promote intensive intellectual interactions among scholars and practitioners from Israel and other countries regarding all aspects of health policy and health care, with a special focus on Israel. During 2012, its first year of operation, the journal succeeded in publishing an impressive volume of policy-relevant articles by a remarkably diverse set of authors. The journal's success to date would not have been possible without the vital contributions of the editorial board, the authors, the reviewers, the readers, BioMed Central (the journal's publisher), and the Israel National Institute for Health Policy (the journal's sponsor). The challenges ahead include promoting greater reader involvement, and enhancing the journal's policy and educational impact.